A Supramolecular Polymer Constituted of Antiaromatic NiII Norcorroles. (21st December 2021) - Ukai, Shusaku; Takamatsu, Aiko; Nobuoka, Masaki; Tsutsui, Yusuke; Fukui, Norihito; Ogi, Soichiro; Seki, Shu; Yamaguchi, Shigehiro; Shinokubo, Hiroshi
Abstract: For the creation of next‐generation organic electronic materials, the integration of π‐systems has recently become a central theme. Such functional materials can be assembled by supramolecular polymerization when aromatic π‐systems are used as monomers, and the properties of the resulting supramolecular polymer strongly depend on the electronic structure of the monomers. Here, we demonstrate the construction of a supramolecular polymer consisting of an antiaromatic π‐system as the monomer. An amide‐functionalized Ni II norcorrole derivative formed a one‐dimensional supramolecular polymer through π‐π stacking and hydrogen‐bonding interactions, ensuring the persistency of the conducting pathway against thermal perturbation, which results in higher charge mobility along the tightly bound linear aggregates than that of the aromatic analogue composed of Zn II porphyrins. Abstract : A supramolecular polymer that consists of an antiaromatic π‐system as the monomer has been created. An amide‐functionalized Ni II norcorrole derivative forms a one‐dimensional supramolecular polymer through π‐π stacking and hydrogen‐bonding interactions. The formation of a long‐range π‐π‐stacking array ensures the persistency of the conducting pathway against thermal perturbation and achieves high charge‐carrier mobility along the tightly‐bound linear aggregates.